If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = -16 + x Solving 19 = -16 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 19 + -1x = -16 + x + -1x Combine like terms: x + -1x = 0 19 + -1x = -16 + 0 19 + -1x = -16 Add '-19' to each side of the equation. 19 + -19 + -1x = -16 + -19 Combine like terms: 19 + -19 = 0 0 + -1x = -16 + -19 -1x = -16 + -19 Combine like terms: -16 + -19 = -35 -1x = -35 Divide each side by '-1'. x = 35 Simplifying x = 35
| 13/8=x/5 | | -6x-3=-3-7(1+x) | | r-(17.5-19r)t=5t^2 | | Ax-7b=2c | | (x+1)*(x-1)=0 | | 40-8m=-8(m-5) | | 40-8m=8(m-5) | | 5q^2+8q=12 | | (5x-1)*(x-1)=0 | | 2x-97=x+4 | | -8+2x=4x-6 | | 2x-95=x+4 | | 6x+8-x=-47 | | 3=5(x-4)+1-4x | | -4x-x=11(4x-11)+4(4-11x) | | 3=5(x-4)*1-4x | | 6m+3n+4m+8n= | | y=x^2-6x+k | | f(x+4)=x^2+2x-8 | | 5-3y+y= | | 65-13.5(0.2P-1.5)=7.5 | | 0.05P+0.07(1200-P)=80 | | 11(1-9x)=-7-12(5x-8) | | -5x+4y= | | 3/6-2/15 | | 152.34=2.95h+72.69 | | 4(3x+1)=5x-8x | | 7x^3e^7x-3x^2e^7x/x^6 | | 11(1+2p)+8(1-7p)=-7p-8p | | (6x^4)-(24x^2)=0 | | x/2=x/3=-10 | | x-1=-3+x |